Pengaruh Penggunaan Presentasi Interaktif Menggunakan Aplikasi Canva Terhadap Hasil Belajar Matematika Peserta Didik Kelas IV SD se-Gugus 1 Kecamatan Serengan - Tri Irawati; Sukarno Sukarno (Didaktika Dwija Indria, 2025)
The purpose of this study is to investigate the effect of using interactive presentations with the Canva application on students' mathematics learning outcomes. This research employs a quantitative approach using a quasi-experimental design, specifically the pretest-posttest control group format. The study involved fourth-grade students from elementary schools within Cluster 1 of Serengan District, selected through a cluster random sampling method. To collect the data, researchers used a multiple-choice test aimed at assessing students’ achievement in mathematics. An independent samples t-test was used to analyze the data. The results demonstrated a statistically significant difference in learning outcomes between the experimental group who were taught using interactive presentations with the Canva application and the control group who were instructed using image-based media. The experimental group scored an average posttest score of 76.52, while the control group scored 63.10, with a significance value of p < 0.001. In summary, the implementation of interactive presentations with the Canva application has a significant influence on elementary school students’ mathematics learning outcomes.